Whole-Genome Sequencing Redefines Shewanella Taxonomy - Thorell, Kaisa; Meier-Kolthoff, Jan P.; Sjöling, Åsa; Martín-Rodríguez, Alberto J. (Frontiers in Microbiology, 2019)
The genus Shewanella encompasses a diverse group of Gram negative, primarily aquatic bacteria with a remarkable ecological relevance, an outstanding set of metabolic features and an emergent clinical importance. The rapid expansion of the genus over the 2000s has prompted questions on the real taxonomic position of some isolates and species. Recent work by us and others have identified inconsistencies in the existing species classification. In this study we have aimed to clarify such issues across the entire genus, making use of the genomic information publicly available worldwide. Phylogenomic analyses, including comparisons based on genome-wide identity indexes (digital DNA-DNA hybridization and Average Nucleotide Identity) combined with core and accessory genome content evaluation suggested that the taxonomic position of 56 of the 112 analyzed strains should be revisited. Based on the genomic information currently available, emended descriptions for some Shewanella species are proposed. Our study establishes for the first time a whole-genome based phylogeny for Shewanella spp. including a classification at the subspecific level.